2003
DOI: 10.1104/pp.009407
|View full text |Cite
|
Sign up to set email alerts
|

RNA Target Sequences Promote Spreading of RNA Silencing

Abstract: It is generally recognized that a silencing-inducing locus can efficiently reduce the expression of genes that give rise to transcripts partially homologous to those produced by the silencing-inducing locus (primary targets). Interestingly, the expression of genes that produce transcripts without homology to the silencing-inducing locus (secondary targets) can also be decreased dramatically via transitive RNA silencing. This phenomenon requires primary target RNAs that contain sequences homologous to secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 57 publications
2
69
0
Order By: Relevance
“…Indeed, previous run-on analyses on methylated versus non-methylated transgenes have revealed that methylation of transcribed sequences does not aVect the rate of transcription (Elmayan et al 1998). However, in one case, methylation has also been shown to spread from coding to promoter sequences, resulting in TGS (Van Houdt et al 2003). It is conceivable that such a spread of methylation from the 271 transgene sequences into the adjacent plant promoter has happened in the epigenetic variant (271*) that we recovered by plating 50,000 hemizygous 271 seeds on a medium supplemented with kanamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous run-on analyses on methylated versus non-methylated transgenes have revealed that methylation of transcribed sequences does not aVect the rate of transcription (Elmayan et al 1998). However, in one case, methylation has also been shown to spread from coding to promoter sequences, resulting in TGS (Van Houdt et al 2003). It is conceivable that such a spread of methylation from the 271 transgene sequences into the adjacent plant promoter has happened in the epigenetic variant (271*) that we recovered by plating 50,000 hemizygous 271 seeds on a medium supplemented with kanamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we study in more detail the 3# to 5# spreading previously observed with the XYZ-silencing system (Van Houdt et al, 2003;Bleys et al, 2006a) by using primary targets Y 98 , Y 250 , and Y 500 in which 98 nt, 250 nt, and 500 nt of the CAT2 sequence, respectively, were inserted between the nptII-3#chs end targeted by the silencing inducer X 21 and the upstream region homologous to a transgenic gus target Z c . We demonstrate that the length of the CAT2 inserts influences the timing and efficiency of silencing induced by secondary CAT2-and gus-specific siRNAs originating from the primary target transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In an XYZ system in tobacco (Nicotiana tabacum), we have shown that transitive amplification products that arise from silenced targets containing transgenic b-glucuronidase (gus) sequences are able to trigger silencing of a gus transgene (Van Houdt et al, 2003). We have now implemented this system in Arabidopsis (Arabidopsis thaliana) and showed that both transgenes and endogenes can be silenced by the secondary transitive signals (Bleys et al, 2006a).…”
mentioning
confidence: 99%
See 2 more Smart Citations